2001
DOI: 10.1073/pnas.141222098
|View full text |Cite
|
Sign up to set email alerts
|

The complete genome of the crenarchaeon Sulfolobus solfataricus P2

Abstract: The genome of the crenarchaeon Sulfolobus solfataricus P2 contains 2,992,245 bp on a single chromosome and encodes 2,977 proteins and many RNAs. One-third of the encoded proteins have no detectable homologs in other sequenced genomes. Moreover, 40% appear to be archaeal-specific, and only 12% and 2.3% are shared exclusively with bacteria and eukarya, respectively. The genome shows a high level of plasticity with 200 diverse insertion sequence elements, many putative nonautonomous mobile elements, and evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
627
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 723 publications
(657 citation statements)
references
References 87 publications
16
627
2
2
Order By: Relevance
“…The advantage of two separate promoters might be an increased metabolic flexibility. Previously, it has been suggested that in S. solfataricus the catabolic EMP pathway is utilized for fructose degradation or other catabolic pathways that proceed via fructose or fructose 6-phosphate (She et al 2001). Therefore an independent regulation of specific genes of the branched ED pathway as well as genes of the common lower shunt of the EMP pathway seem to be favorable in order to adapt and respond to different carbon sources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of two separate promoters might be an increased metabolic flexibility. Previously, it has been suggested that in S. solfataricus the catabolic EMP pathway is utilized for fructose degradation or other catabolic pathways that proceed via fructose or fructose 6-phosphate (She et al 2001). Therefore an independent regulation of specific genes of the branched ED pathway as well as genes of the common lower shunt of the EMP pathway seem to be favorable in order to adapt and respond to different carbon sources.…”
Section: Resultsmentioning
confidence: 99%
“…The EMP pathway is supposed to be active only in gluconeogenetic direction allowing for glycogen formation and for the degradation of fructose or alternative substrates (e.g. sucrose; She et al 2001). For the conversion of glucose to fructose 1,6-bisphosphate respective sugar kinases are missing.…”
Section: Enzyme Characterizationmentioning
confidence: 99%
“…With respect to the cysteine residues, this potential mechanism is somewhat analogous to that in peroxiredoxins such as alkyl hydroperoxidase C (AhpC) (48,49), the thioredoxin-linked peroxidase activity of Tpx (50,51), or the thioredoxin dependent activity of bacterioferritin comigratory proteins (52). A number of thioredoxin, glutaredoxin, and ferredoxin type molecules have been annotated in the Sulfolobus solfataricus genome; this includes thioredoxins a, b, and c, and a protein disulfide oxidoreductase (15). Although speculative, this scheme is consistent with increased expression of SsDPSL in response to hydrogen peroxide under iron-limiting conditions.…”
Section: H 2 O 2 + 2r ′ Sh → + 2 H 2 O + R ′ Ssr ′ (Viii)mentioning
confidence: 99%
“…The only family of cultured acidophiles among the Crenarchaeota are the Sulfolobaceae, which grow at pH 2-4 (Makarova and Koonin 2003;Makarova and Koonin 2005;She et al 2001). The Euryarchaeota contains several members that grow at extremely low pH, including F. acidarmanus Fer1 and the other identified member of this family, F. acidiphilum (Edwards et al 2000;Golyshina and Timmis 2005).…”
Section: Introductionmentioning
confidence: 99%